Ultrafast high-temperature sintering: Principles, advantages, and applications - Shen, Hui-Zhen; Zhao, Liang; Kong, Xiang-Rui; Guo, Rui-Fen; Shen, Ping (Journal of the European Ceramic Society, 2025)
Conventional ceramic sintering is fundamentally limited by prolonged high-temperature durations, high energy consumption, and detrimental microstructural evolution. To overcome these challenges, Ultrafast High-temperature Sintering (UHS), first introduced in 2020, presents a transformative solution. Utilizing Joule-heated carbon/graphite felts/papers, UHS achieves unprecedented heating/cooling rates (103−104 oC/min) and extreme temperatures (∼ 3000 °C), enabling ceramic synthesis and densification within seconds to minutes. This review provides a systematic overview of UHS, detailing equipment design, temperature measurement, fundamental principles, key processing parameters, technical advantages and limitations, and research progress. The technique’s ultra-rapid heating rates are central to its efficacy, effectively bypassing slow surface diffusion pathways to activate faster grain boundary and lattice diffusion, leading to accelerated densification and precise microstructural control. These unique capabilities have enabled the rapid fabrication of diverse materials, demonstrating significant impact across critical application fields. Although challenges persist, UHS establishes a new paradigm for sustainable manufacturing, high-throughput material discovery, and complex ceramic processing. •UHS: Ultrafast ceramic sintering (seconds/minutes) via Joule heating.•UHS mechanism: Rapid heating activates fast diffusion pathways.•UHS enables refined microstructure and suppressed volatile loss.•UHS applied to diverse oxides, carbides, borides, nitrides, etc.•UHS advances solid electrolytes, TBCs, dielectric ceramics, etc.